Investigating the Relationship between Hajj Pilgrimage and Mental Health among Sharif University of Technology Students - Maryam Bakhtiari; Abbas Masjedi Arani; Marzieh Karamkhani; Masume Shokri Khubestani; Hossein Mohammadi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: The significance of research into psychological aspects of Hajj pilgrimage and its rituals is rooted in the psychological importance of religion as a complete set of programs for human's life. Given that, this study has set out to examine the relationship between Hajj pilgrimage and mental health among the students of Sharif University of Technology. Method: This applied research adopted a descriptive - correlational design. 350 students (male = 84, female = 266) were randomly selected to participate in this study. After selecting the representative population, the related questionnaires were completed by the participants before and after Hajj pilgrimage to gather the required data. In doing so, the General Health Questionnaire (GHQ) and Meaning in Life Questionnaire were administered. Finally, the data using SPSS statistical software and descriptive statistical techniques (the mean and standard deviation) and inferential statistical method (t-test) were analyzed. In this study, all the ethical issues were considered; besides, the authors declared no conflict of interest. Results: The results indicated that there was a significant increase in the participants' mean score of mental health and meaning in life. Moreover, Hajj pilgrimage increased the mental health and meaning in life. Conclusion: Findings of this study revealed that pilgrimage to Mecca lowers anxiety, depression, and stress. Furthermore, it raises social functioning and meaning in life. In fact, pilgrimage is one of the most important religious practices to improve mental health, which needs to be taken into account when interventions toward mental health are intended. For downloading the full-text of this article please click here.